Hydrotechnical construction, water engineering and water technologies: some modern issues and training of professionals - Riazantsev , O.; Shylin , V. (New Collegium, 2021)
The article considers modern problems and problems that currently exist in hydraulic engineering and hydropower, problems of land and water resources. And also problems of training of experts. able to solve these problems Recently, the problems caused by existing large hydraulic structures are increasingly mentioned. The main problem is that the nodes of hydraulic structures often form artificial reservoirs of a large plane. It often happens that the depths of reservoirs are insignificant. This situation is very unsatisfactory because the land is used irrationally. which is a valuable resource and has a high cost and can be used effectively for agriculture. Creation of hydraulic structures, complexes of hydraulic structures significantly change the hydrological, biological. salt and thermal regimes of the river on which they are built, the regime of groundwater movement, cause climate change in the surrounding areas. Cascades of hydraulic structures have a special influence. As an example, we can cite the Dnieper cascade of hydroelectric power plants and compare the area of its reservoirs and the amount of electricity generated by its power plants with the world's largest hydroelectric power plants. In addition, shallow water bodies cause a significant deterioration in water quality. And since reservoirs are often a source of water supply for settlements and industrial enterprises, this situation is controversial. Intensive construction of hydraulic structures and their complexes took place during the twentieth century, many of them exhausted their resources and needed either reconstruction or decommissioning. The reasons for this state of affairs are the development of technology, the emergence and development of other alternative energy sources for thermal and nuclear power plants, other than hydraulic. Also, since the construction of many buildings, approaches to determining their profitability and efficiency have changed. Aspects of training specialists in hydraulic engineering and water engineering, able to solve these problems of the industry today, and those that will face them in the near future are considered. The ability of a competent professional to anticipate the consequences of any action must be an integral part of it. Attention is drawn to the need to apply conceptually new approaches to solving problems of construction of new hydraulic and hydropower facilities, operation and reconstruction of existing facilities.